Magrib Reciting Quran Education Program as an Attempt to Build Children's Character in Walahar Village, Gempol District, Cirebon Regency: Program Pendidikan Magrib Mengaji Sebagai Upaya Pembentukan Karakter Anak di Desa Walahar Kecamatan Gempol Kabupaten Cirebon - Fajriyah, Euis; Rubiyad, Adib; Rofiq, Ainur (Yayasan Sagita Akademia Maju, 2025)
Religious education is a great foundation to children's character and personality building. Religious education in the community is carried out through various activities, including the Maghrib Reciting Quran education program. The Maghrib Reciting Quran education program is carried out as an effort to children's character building in Walahar Village, Gempol District, Cirebon Regency. The method used in this PkM is Participatory Action Research (PAR). The Maghrib Reciting Quran activity is carried out after the Maghrib prayer in congregation by introducing the hijaiyah letters for children who are not yet able and not yet fluent in reading the Quran. Through the Maghrib Reciting Quran education program, children’s characters building are: (1) Religious, (2) Disciplined, (3) Tolerant, (4) National spirit, (5) Hard work, (6) Cooperation, (7) Friendly, (8) Love peace, (9) Love to reciting Quran, (10) Respect each other, (11) Care for the environment, and (12) Care for society.